Strategi Imitasi dan Kesuksesan UKM? Perspektif Kewirausahaan - Rina Sulistiyani (STIE Kertanegara Malang, 2022)
The imitation strategy has become the best strategy to catch up with the market leader. The phenomenon of imitation strategy is also still dominantly carried out by Small and Medium Enterprises in the Tanggulangin Sidoarjo bag and luggage center area. This study aims to reveal the attitude of the craftsmen towards the imitation strategy and the experiences of the craftsmen while carrying out the imitation strategy from an entrepreneurial perspective. The research uses an interpretive paradigm and a phenomenological approach. data collection through in-depth interviews, observation and documentation. Data analysis refers to the Creswell analysis technique and the unit of analysis is bag and suitcase craftsmen. The research findings show that the imitation strategy is responded positively by the craftsmen who are supported by the spirit of learning and the spirit to progress. The experience of implementing imitation strategies is manifested in the themes of profit opportunities, market access, learning from failure, liking challenges, long-term orientation and hard work. The originality of the research succeeded in revealing the entrepreneurial values that accompany the successful implementation of the imitation strategy.Keywords: entrepreneurship, imitation strategies, success